2022
DOI: 10.1186/s13012-022-01221-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a tailored sepsis treatment protocol on patient outcomes in the Tikur Anbessa Specialized Hospital, Ethiopia: results of an interrupted time series analysis

Abstract: Background Despite improvement, sepsis mortality rates remain high, with an estimated 11 million sepsis-related deaths globally in 2017 (Rudd et. al, Lancet 395:200-211, 2020). Low- and middle-income countries (LMICs) are estimated to account for 85% of global sepsis mortality; however, evidence for improved sepsis mortality in LMICs is lacking. We aimed to improve sepsis care and outcomes through development and evaluation of a sepsis treatment protocol tailored to the Tikur Anbessa Specialize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, it is di cult to conclude without controlling the effect of other treatment-related factors. Some studies have shown the negative effect of delayed initiation of antimicrobial in determining the outcome of septic shock [9,20]. This effect was absent in our study probably because that antimicrobials were initiated within the rst 3 hours of diagnosis nearly for all cases (95%) in line with the 3-hour sepsis bundle.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, it is di cult to conclude without controlling the effect of other treatment-related factors. Some studies have shown the negative effect of delayed initiation of antimicrobial in determining the outcome of septic shock [9,20]. This effect was absent in our study probably because that antimicrobials were initiated within the rst 3 hours of diagnosis nearly for all cases (95%) in line with the 3-hour sepsis bundle.…”
Section: Discussionmentioning
confidence: 54%
“…Besides, the absence of well-customized hospital-based protocols for early identi cation and management of septic shock may contribute to higher mortality. In addition to limited knowledge and resources, septic shock mortality in Sub-Saharan Africa is believed to be disproportionately high due to widespread malnutrition, sub-optimally managed comorbidities and higher rates of infectious diseases including HIV and TB [4,5,8,9]. Around 68% of patients had one or more comorbidities and HIV was found in 18.8% of the cases in our study.…”
Section: Discussionmentioning
confidence: 65%
“…Choosing to leave your job is a cognitive process, and withdrawal is exhibited by quitting the existing job or pursuing other opportunities (Liu and Raghuram, 2022). In studies conducted worldwide, a high incidence of turnover (ranging from 18 to 68% ) among nurses has been noted (Puchalski Ritchie et al, 2022). In this study, we will analyze the prevalence of turnover intention and factors contributing to it among emergency nurses working in a government hospital.…”
Section: Introductionmentioning
confidence: 99%
“…There is certainly room for more research, and guidelines and education based on that research. Quality and safety improvement in LMIC is challenging because of lack of human resources, as detailed in this negative pre-post sepsis guidelines implementation study in Ethiopia resulting in no outcomes improvement [6].…”
mentioning
confidence: 99%